東南極海氷内部領域の氷盤分布の特徴 - 豊田, 威信; アリソン, コホウト; アレクサンダー, フレーザー; Toyota, Takenobu; Kohout, Alison; Fraser, Alexander (2013)
To understand the wave - ice interaction and then the formation process of floe size distribution (FSD) in the marginal ice zone (MIZ), we planned to conduct the concurrent measurements of FSD and wave activities off East Antarctica during the Sea Ice Physics and Ecosystem Experiment 2 (SIPEX2) in September to November 2012 for the first time. There, FSD was measured by a heli-borne video camera, while the wave activities were monitored by deploying five vertical accelerators in MIZ. While the wave activity measurements were successful to some extent, unfortunately the measurement of FSD could be achieved only in the two interior ice regions about 200 km away from the ice edge due to the bad weather conditions. Therefore in this study we include satellite MODIS images (horizontal resolution: 250 m, wide-swath coverage but cloud-affected) to examine the evolution of FSD with time in the interior ice regions for relatively large floes. Through image processing analysis, the quantitative properties of FSD will be shown and the role of MIZ in the ice extent retreat will be discussed. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月15日（金） 国立極地研究所 ３階ラウンジ conference object